Pre-service mathematics teachers' abstraction of rotational symmetry - Gülşade Savaş; Nilüfer Yavuzsoy Köse (Journal of Pedagogical Research, 2023)
This study investigates first-year undergraduate students of Primary Education Mathematics Teacher Education's knowledge and understanding of rotational symmetry in geometric shapes. Three students participated in this study, which was designed within the framework of a one-to-one teaching experiment (a qualitative research method) in the fall semester of the 2020-2021 academic year. A total of four one-to-one clinical interviews were conducted with the students once a week for an average of one hour and fifteen minutes each. Researchers recorded the sessions with a video camera and kept a log of observations. The data were analyzed and interpreted using continuous analysis and retrospective analysis. Each abstraction type and level of rotational symmetry was assigned indicators based on the results. According to the results, a student at Piaget's experimental abstraction level related to rotational symmetry before the teaching experiment reached the third level of reflective abstraction. Another student at experimental abstraction reached the level of reflective abstraction at level 2; the student who was not at any level reached the level of reflective abstraction at level 1. Students can undertake reflective abstraction by improving their knowledge and understanding of rotational symmetry by using daily life examples and making rotational symmetric drawings in the classroom. Consequently, daily life examples should be used more often in geometry lessons and students should be encouraged to draw more. Additionally, it was suggested that new research be conducted to support student abstraction based on Piaget's reflective abstraction theory.